Bioartificial polymeric materials based on collagen and poly(N-isopropylacrylamide) - Mano,Valdir (2007)
Films of collagen (CLG) and poly(N-isopropylacrylamide), PNIPAAm, were prepared by casting from water solutions. These bioartificial polymeric materials were studied to examine the influence of PNIPAAm content and glutaraldehyde vapor cross-linking on the thermal and biological stability of CLG. Mixtures, ranging from 20-80 wt% CLG composition, were cross-linked through exposure to glutaraldehyde vapors. Thermal and morphological properties of the films, cross-linked or not, were investigated by differential scanning calorimetry, thermogravimetry, and scanning electron microscopy, with the aim of evaluating miscibility, thermal stability, and interactions among the constituents. The experimental results indicated that the homopolymers are not thermodynamically compatible. However, there is good evidence that effective interactions, probably due to hydrogen bond formation, takes place between the constituents. These interactions are more evident on the samples that were not cross-linked. DSC studies revealed that PNIPAAm exerts a thermal stabilizing effect on uncross-linked CLG, while the cross-linking with glutaraldehyde affects only the biological polymer, preventing the interactions with PNIPAAm. SEM micrographs of the uncross-linked mixtures showed that the morphology, in all compositions studied, remains similar to the pure collagen. In the corresponding cross-linked samples, a more compact aggregation is observed although no appreciably changes can be seen.